2017
DOI: 10.1016/j.meatsci.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory growth in crossbred Aberdeen Angus and Belgian Blue steers: Effects on the colour, shear force and sensory characteristics of longissimus muscle

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. The effect of feed restriction (99 days) followed by compensatory growth during a 27 200 day re-alimentation period on the colour and sensory characteristics of meat from 28Aberdeen Angus × Holstein-Friesian (AN) and Belgian Blue × Holstein-Friesian (BB) 29 steers was examined. Compensatory growth had no effect on muscle pH and 30 temperature decline, chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
3
11
5
Order By: Relevance
“…Chambaz et al (2003) compared the WBSF of LT from Angus, Charolais, Limousin and Simmental steers slaughtered at a common IMF concentration (32.5 g/kg) and found no difference. In contrast to the present study, Keady et al (2017) reported lower WBSF for LT from Angus-sired steers than from Belgian Blue sired steers after 14 d ageing, which likely reflects the greater difference in IMF content in the two studies. The effect of later slaughter (increasing slaughter age/weight) on IMF content and collagen solubility was as expected (Maltin et al, 1998;Mezgebo et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Chambaz et al (2003) compared the WBSF of LT from Angus, Charolais, Limousin and Simmental steers slaughtered at a common IMF concentration (32.5 g/kg) and found no difference. In contrast to the present study, Keady et al (2017) reported lower WBSF for LT from Angus-sired steers than from Belgian Blue sired steers after 14 d ageing, which likely reflects the greater difference in IMF content in the two studies. The effect of later slaughter (increasing slaughter age/weight) on IMF content and collagen solubility was as expected (Maltin et al, 1998;Mezgebo et al, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…An objective, standardised instrumental approach was used to directly measure toughness to allow comparison with the literature but also because of the practical constraints to carrying out trained sensory panel or consumer assessment of the large sample set used. As expected, the sire breeds resulted in differences in carcass characteristics which are qualitatively similar to those reported for dairy origin steers sired by Angus or Belgian Blue bulls (Keady et al, 2017). The size of the difference between sire breeds in LT IMF content across both studies reflects the different genders and experimental designs (59.6 vs. 39.1 in the present study and 74.5 vs. 36.4 g/kg in Keady et al (2017) for Angus and Belgian Blue sires, respectively).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have highlighted the role of compensatory growth when estimating beef cattle performance (Hoch and Agabriel, 2004;Keele et al, 1992;Oltjen et al, 1986). In addition, compensatory growth could influence a farm' financial performance (Ashfield et al, 2014b), as it can be employed as a strategy to reduce feeding costs (Lopes et al, 2018), and it was found to have an effect on meat's sensory characteristics and quality (Keady et al, 2017). The variability in experimentally-derived growth curves was a result of actual feed availability, and this was particularly obvious for the long-duration finishing systems which incorporated two grazing periods.…”
Section: Origin Of Experimental Datamentioning
confidence: 99%
“…Meat quality is important for consumers and feeding strategy can provide further enrichment (Dalle Zotte et al 2020). A minor effect of FR on physical meat quality characteristics has been described in chickens (Gratta et al 2019), rabbits (Gidenne et al 2012;Chodova et al 2019) and cattle (Keady et al 2017). Inconsistent data were documented for the meat nutritional value in rabbits.…”
mentioning
confidence: 99%